Implementasi Pendidikan Karakter Islami melalui Integrasi Tahfiz dan Pembelajaran PAI di MA (Madrasah Aliyah) An Nur Prima (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to analyze the implementation of Islamic character education through the integration of the Qur’an memorization program (Tahfiz al-Qur’an) and Islamic Religious Education (PAI) at MA An Nur Prima, Medan, North Sumatra. The institution adopts a unique curriculum model in which students participate in Tahfiz activities every morning from 08:00 to 11:00, followed by formal learning, including PAI subjects, from 11:00 to 15:00. This design reflects a systematic effort to instill Islamic values through intensive interaction with the Qur’an while ensuring the achievement of academic competencies. Using a descriptive qualitative approach, data were collected through participatory observation, semi-structured interviews, and documentation during a four-week Professional Capacity Development (PKP) program. The findings show that Islamic character values such as discipline, responsibility, patience, perseverance, and love for the Qur’an were successfully cultivated through the synergy between the Tahfiz program and PAI instruction. Supporting factors included structured school discipline, strong collaboration between Tahfiz supervisors and PAI teachers, as well as high levels of students’ spiritual motivation. However, several challenges emerged, such as student fatigue, reduced concentration in afternoon classes, and differences in self-regulation skills. To address these issues, the school and teachers applied strategies such as providing an ISHOMA break, have lunch (rest, prayer, and meal), encouraging congregational Zuhur prayer, supplying meals to restore energy, incorporating ice-breaking activities, and designing interactive and engaging learning sessions. In conclusion, the integration of Tahfiz al-Qur’an and PAI proved effective in developing Islamic character values while maintaining a balance between students’ spiritual formation and academic performance.